High‐performance detection of an abdominal aortic aneurysm biomarker by immunosensing. (9th January 2020) - Guo, Shikui; Li, Yuejin; Li, Rougang; Zhang, Peng; Wang, Yongzhi; Gopinath, Subash C.B.; Gong, Kunmei; Wan, Ping
Abstract: Abdominal aortic aneurysm (AAA) is a serious, life‐threatening vascular disease that presents as an enlarged area of the aorta, which is the main artery that carries blood away from the heart. AAA may occur at any location in the aorta, but it is mainly found in the abdominal region. A ruptured AAA causes serious health issues, including death. Traditional imaging techniques, such as computed tomography angiogram, magnetic resonance imaging, and ultrasound sonography, have been used to identify AAAs. Circulating biomarkers have recently become attractive for diagnosing AAAs due to their cost‐effectiveness compared to imaging. Insulin‐like growth factor 1 (IGF‐1), a secreted hormone vital for human atherosclerotic plaque stability, has been found to be an efficient biomarker for AAA identification. In this report, immunosensing was performed by using an InterDigitated electrode (IDE) sensor to detect circulating levels of IGF‐1. The detection limit of IGF‐1 was found to be 100 fM with this sensor. Moreover, related protein controls (IGF‐2 and IGFBP3) were not detected with the same antibody, indicating selective IGF‐1 detection. Thus, immunosensing by using an IDE sensor may help to effectively diagnose AAAs and represents a basic platform for further development. Abstract : High‐performance detection of an abdominal aortic aneurysm.